Impact of NPK fertilization on hazelnut yield and soil chemical-microbiological properties of Hazelnut Orchards in Western Georgia - Rıdvan Kızılkaya; Guguli Dumbadze; Coşkun Gülser; Lali Jgenti (Eurasian Journal of Soil Science, 2022)
In this study, the effects of ground and foliar applications of the NPK fertilizers in hazelnut orchards on the soil chemical and microbiological properties and hazelnut yield were investigated. The fertilization practicesses from ground were done two times using NPK (20:10:10 +trace elements) on March and May while the fertilization practices from leaf were done three times using NK (15:12 +trace elements) on May, June and July at six different hazelnut orchards located on Samegrelo, Guria and Adjara regions in Western Georgia in 2018. The alkaline characterized fertilizer applications from soil generally increased soil reaction (pH), nutrient contents and EC values in different magnitude depends on the soil characteristics of locations. The lowest soil pH (4,40) and EC (0,107 dS m-1) values showed the highest increment (10,7% and 77,6%, respectively) over the control. The basal soil respiration and Cmic values of all hazelnut orchards were generally increased by the NPK ferilization. Increasing soil pH and EC by the fertilization also increased CA and DHA activity. The mean values of percent increase in yield and yield parameters by the NPK fertilization were obtained as 8,3% in yield, 13,3% in shelled nut weight, 10,0% in kernel weight and 5,1% in percent kernel efficiency. The hazelnut yield value had significant positive correlation with soil pH (0,669*), EC (0,652*) and Cmic (0,620*) values. The foliar fertilization and improving the soil properties of hazelnut orchards by the application of alkaline characteristic NPK fertilizer from soil increased hazelnut yield and yield parameters compare with the farmer applications or control treatments. The increments in soil microbiological properties and nutrients are considered as a desirable result in terms of sustainable soil management and plant nutrition for hazelnut orchards.